2012
DOI: 10.1007/s10815-012-9833-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of EG-VEGF, VEGF and TGF-β1 on pregnancy outcome in patients undergoing IVF-ET treatment

Abstract: Purpose To investigate the correlation of endocrine glandderived vascular endothelial growth factor (EG-VEGF), vascular endothelial growth factor (VEGF) and transforming growth factor beta 1 (TGF-β1) with the corresponding reproductive outcome in patients who received in vitro fertilizationembryo transfer (IVF-ET). Methods Sixty-seven women undergoing IVF-ET at a university tertiary hospital were recruited for a prospective study. Concentrations of EG-VEGF, VEGF and TGF-β1 were measured by enzyme-linked immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…Even intrafollicular ADM concentration is suggested to be independent of ovarian function parameters [42]. In contrast, a recent study has established a negative correlation between intrafollicular VEGF and ovarian response and oocyte maturation [43]. Also, increased ADM in follicular fluid is associated with a negative IVF outcome [44].…”
Section: Discussionmentioning
confidence: 98%
“…Even intrafollicular ADM concentration is suggested to be independent of ovarian function parameters [42]. In contrast, a recent study has established a negative correlation between intrafollicular VEGF and ovarian response and oocyte maturation [43]. Also, increased ADM in follicular fluid is associated with a negative IVF outcome [44].…”
Section: Discussionmentioning
confidence: 98%
“…In this study, follicular fluid EG-VEGF levels increased significantly in the WVFs (1905 ± 243.8 vs. 1586 ± 705.2, p = 0.008), but the FF EG-VEGF levels were similar in the conceptus/ nonconceptus cycles (p > 0.05). A previous study of EG-VEGF levels in follicular fluid and IVF outcomes found a negative correlation between EG-VEGF, VEGF, and oocyte maturity but a positive correlation with embryo quality [11]. The same study reported increased serum EG-VEGF levels in pregnant cases.…”
Section: Discussionmentioning
confidence: 67%
“…EG-VEGF, also known as prokineticin [9], is an EGspecific vasoactive substance [10]. The expression of EG-VEGF in ovarian tissue was previously reported to be correlated with VEGF [11,12]. In this study, follicular fluid EG-VEGF levels increased significantly in the WVFs (1905 ± 243.8 vs. 1586 ± 705.2, p = 0.008), but the FF EG-VEGF levels were similar in the conceptus/ nonconceptus cycles (p > 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations